Ipsa and Odong: Decorative metalwork of Korea - Paul T. Craddock; Alessandra Giumlia-Mair (Advances in Archaeomaterials, 2023)
Inlay and patination are important elements in the prestige metalwork of East and Southeast Asia. There are several regional varieties, but they have many features in common, particularly in the use of a patinated copper alloy containing small amounts of gold. This in turn may suggest a common or at least linked ancestry, but probably no earlier than the sixteenth century. Most of this metalwork is no longer produced, but in Korea, production is still practised, albeit on a small scale. Based on the authors’ visits to workshops producing these items, this paper describes the present production of ipsa and odong. In ipsa pieces, wires—usually made of silver, gold, or brass—are hammered into the chased surface of the body metal, predominantly copper alloy or iron, which is then patinated. Odong items are usually complex composites made of several separate parts carefully soldered together in stages. An odong is an artificially patinated special copper alloy containing small amounts of gold, into which silver can be inlaid. Conversely, an odong can itself be inlaid into silver. Then follows a complex process to develop the deep purple-black patination common to all these traditional pieces produced in East and Southeast Asia.